Green Fluorescent Protein-Mediated Biomineralization of Silver Microparticles - Cabiles, Ma. Monica M.; Lira, Brandon Cyril S.; Janairo, Jose Isagani B. (Orbital: The Electronic Journal of Chemistry, 2021)
Biomineralization is a bio-inspired technique of creating inorganic nanostructures using peptides or proteins. An important consideration in selecting a biomineralization agent is the overall shape or geometry of the protein since this can influence the properties of the produced nanostructures. The green fluorescent protein (GFP) from the jellyfish Aequorea victoria is a promising biomineralization agent due to its distinct structure, characterized by having a barrel-like structure. In this study, silver microparticles (AgMPs) with a diameter of 500 nm were produced through GFP-mediated biomineralization under ambient reaction conditions. In the absence of GFP, aggregated and disordered silver structures were formed. A proposed model to account for the observation involves the formation of GFP networks to which growing silver particles may become adsorbed to. The presented study provides the motivation for the further study of using GFP towards nanostructure synthesis. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1574